2004
DOI: 10.1111/j.1601-5223.1997.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Evaluation of 20 Primary Breast Carcinomas

Abstract: Chromosome analysis was performed on samples from 20 Brazilian patients with breast cancer. All the samples were from untreated patients who presented the clinical symptoms for months or years before surgical intervention. Six cases showed axillary lymph node metastases. Clonal chromosome abnormalities were detected in all cases. The numerical alterations most frequently observed involved the loss of chromosomes X, 19, 20, and 22 followed by gain of chromosomes 9 and 8. Among the structural anomalies observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, we note that ASCAT used additional information (B-allele frequencies), while THetA, CNAnorm and ABSOLUTE used only read depth. The identified aberrations do not distinguish between those in different subpopulations, but do include several previously reported in breast cancer [42-47]. We also ran THetA using chromosome arms as the intervals, rather than the BIC-Seq intervals.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we note that ASCAT used additional information (B-allele frequencies), while THetA, CNAnorm and ABSOLUTE used only read depth. The identified aberrations do not distinguish between those in different subpopulations, but do include several previously reported in breast cancer [42-47]. We also ran THetA using chromosome arms as the intervals, rather than the BIC-Seq intervals.…”
Section: Resultsmentioning
confidence: 99%
“…21 The methodology and the technical conditions that are used for culturing the tumour cells, including the time of growth in vitro, can result in the growth of cells with normal karyotypes or with no clonal chromosomal abnormalities. [22][23][24] The meaning of such findings remains controversial, and it is not known whether these cells with normal karyotypes are of neoplastic origin or whether selection for non-neoplastic cells occurs during in vitro culture, as suggested by Truong et al 21 Recently, it was shown by Kleivi and colleagues 18 that cases of breast cancer that presented normal cells by classic cytogenetic analysis were not really karyotypically normal, but had genetic alterations when CGH analysis was carried out. In our study, CGH showed the presence of genetic imbalances in all three cases studied, reflecting the presence of these aberrations in a high proportion of the tumour cells (usually over 50%), but not in every cell.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified a number of DNA copy number changes that are recurrent in primary breast tumors. The most frequent of these abnormalities, which have been correlated with lymph node status, are presented in Table 1 and Figures 1 & 2. DNA copy number changes associated with axillary lymph nodes status Studies using conventional cytogenetics were the first to report chromosomal alterations associated with clinico-histopathological parameters, including axillary lymph node status [149][150][151][152][153][154][155][156]. In these reports, GTG banding ana lysis of the primary tumors from patients with lymph node metastasis revealed mostly losses of chromosomes 17, 19, 21, 22 and X, and gains of chromosomes Review Cavalli 9 and 18.…”
Section: Reviewmentioning
confidence: 99%